P120 Observational study of acute admissions with non-infective asthma and COPD to Perth Royal Infirmary following the eruption of Icelandic volcano Eyjafjallajokull and subsequent ash cloud formation. (16th November 2010) - Wilkie, M E M; Anderson, M; Schembri, S
Abstract : Introduction and objectives: Eyjafjallajokull, a volcano in Iceland erupted on the 20th March 2010 after a prolonged period of seismic activity starting late 2009. Subsequent ash cloud formation on 14th April caused considerable disruption to Scottish and European airspace. Studies performed in Japan and the British West Indies showed that noxious by-products including sulphur dioxide, have a significant impact on asthma and COPD admissions and severity.1 2 The aim of this study was to record trends of hospitalisation for non-infective exacerbations of asthma and COPD from eruption until volcano quiescence. Methods: Data of all patients admitted to PRI over the period of 20 March 2010 to 31 May 2010 with shortness of breath was collected. Patients included were those with a diagnosis of non-infective asthma or COPD. Other admission diagnoses were excluded. We recorded diagnosis, age and sex. Results: 100 patients were admitted with shortness of breath during the study period. 12 patients were diagnosed with non-infective asthma (mean age 52, M:F=5:7) and 17 with non infective COPD (mean age 76, M:F=5:12). The preponderance of female admissions has been noted in previous studies.2 Ash cloud formation occurred at day 26 with closure of Scottish airports at day 27, 45, 51 and 58. Ash production subsided day 63. We observed a cluster of admissions from day 22 to day 37. Conclusions: The cluster of admissions associated with ash cloud presence suggests the possibility of a causative effect. Our study is however limited by the duration of data collection and the absence of a comparative data from previous years.